2019
DOI: 10.1002/lsm.23096
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Lipid Profiles of Picosecond Infrared Laser‐Generated Tissue Aerosols Discriminate Different Brain Tissues

Abstract: Background and Objectives A picosecond infrared laser (PIRL) has recently been demonstrated to cut biological tissue without scar formation based on the minimal destructive action on the surrounding cells. During cutting with PIRL, the irradiated tissue is ablated by a cold vaporization process termed desorption by impulsive vibrational excitation. In the resulting aerosol, all molecules are dissolved in small droplets and even labile biomolecules like proteins remain intact after ablation. It is hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Compared to mechanical homogenization, this is a very gentle method of sample extraction and homogenization, avoiding time-consuming preparation steps. Over the past decade, this tissue sampling and homogenization has been successfully demonstrated with a PIRL, nanosecond infrared laser (NIRL) and even a high-energy microsecond infrared laser (MIRL) with subsequent mass spectrometric proteomics [ 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] or directly coupled to real-time MS instruments, such as the “SpiderMass” technology [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to mechanical homogenization, this is a very gentle method of sample extraction and homogenization, avoiding time-consuming preparation steps. Over the past decade, this tissue sampling and homogenization has been successfully demonstrated with a PIRL, nanosecond infrared laser (NIRL) and even a high-energy microsecond infrared laser (MIRL) with subsequent mass spectrometric proteomics [ 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] or directly coupled to real-time MS instruments, such as the “SpiderMass” technology [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies we utilized a picosecond infrared laser (PIRL) [ 4 , 13 , 16 , 19 ] as well as a microsecond infrared laser (MIRL) [ 15 , 16 ] for tissue sampling and homogenization for subsequent proteomics and lipidomics. In a first study by Kwiatkowski et al (2015), it was shown that tissue sampling with the PIRL makes proteins accessible in a wide range from a few kilodaltons to several million daltons.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the smallest reported sample volume for shotgun lipidomics with IRL-based tissue sampling, thus demonstrating the enormous potential of spatial lipidomics. The approach is much faster than classical mechanical homogenization and more volume efficient than the IRL-based sampling described in our previous study, which had an ablation volume of 1 mL (a factor of 2000) and utilized an aerosol cryotrap [40].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the resulting high cutting precision and significant superiority concerning wound healing and scar formation compared with other lasers, the application of DIVE generates an aerosol that is particularly suitable for subsequent differential quantitative proteomics and lipidomics. Several studies have tested the function of real-time MS concepts for tissue differentiation [32,40,41]. Utilizing laser-based aerosolization [12,42,43] or tissue surface extraction [33] combined with real-time MS enables the characterization of different tissue pathologies (cancer, infection, or inflammation) within seconds based on lipid profile signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research have demonstrated the use of mass spectrum coupled with a PIRL-based laser scalpel in discriminating different brain areas. 34 Cancer screening of body fluids was the other possible way using mass spectrum which may improve the survival time prognosis of patients. The pathologic confirmation of the diagnosis is necessary before any non-surgical treatment and can be challenging in ICC.…”
mentioning
confidence: 99%